The anticipated thought of Miguel Delibes and "El mundo que agoniza" - Egido, Aurora (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The concern for Nature and for the harmful effects of a poorly understood «progress» is a constant in the work of Miguel Delibes. His narrative and his thought vindicate literature and humanities as a means to denounce the imminent ecological disaster, as well as to provide possible solutions.
Keywords: Miguel Delibes; El mundo que agoniza; Nature; ecology